2014
DOI: 10.1299/jamdsm.2014jamdsm0042
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nanoparticle additives on rough surface cylinder in line contact under TEHL with non-Newtonian lubricant

Abstract: This paper presents the results of a transient analysis of thermal elastohydrodynamic lubrication (TEHL) of a rough cylinder on a rough flat surface in line contact with non-Newtonian lubricant blended with Al 2 O 3 nanoparticles. The simultaneous systems of time-dependent modified Reynolds equation, elasticity equation and energy equation with initial conditions were solved numerically using multigrid multilevel with full approximation technique. In this study, the effect of Al 2 O 3 nanoparticle additives, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
0
0
Order By: Relevance
“…Thermal conductivity and viscosity of nanofluids increase significantly with nanoparticles volume concentration presented by Murshed [7] and Chandrasekar [8]. Mongkolwongrojn [9] showed that the TEHL with Al2O3 nanoparticle additives for low slip/slide ration condition, the film temperature increases very little due to thermal enhancement of nanofluids. The multigrid algorithm is more efficient than the Newton-Raphsonmethod in solving EHL with roughness effect presented by Lubrecht [10].…”
Section: Introductionmentioning
confidence: 95%
“…Thermal conductivity and viscosity of nanofluids increase significantly with nanoparticles volume concentration presented by Murshed [7] and Chandrasekar [8]. Mongkolwongrojn [9] showed that the TEHL with Al2O3 nanoparticle additives for low slip/slide ration condition, the film temperature increases very little due to thermal enhancement of nanofluids. The multigrid algorithm is more efficient than the Newton-Raphsonmethod in solving EHL with roughness effect presented by Lubrecht [10].…”
Section: Introductionmentioning
confidence: 95%